AKUNTABILITAS LEMBAGA AMIL ZAKAT DALAM PERSPEKTIF MAQASHID SYARIAH (STUDI PADA YAYASAN DANA SOSIAL AL FALAH SURABAYA) - ASMARANI, MARLIA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to determine the accountability of the amil zakat institution (LAZ) Al Falah Social Fund Foundation (YDSF). The research method uses a qualitative phenomenological approach. The data in this study were obtained through direct and indirect interviews with informants directly related to the object of research, namely LAZ YDSF. The results showed that accountability practices were carried out as they should. Shariah Enterprise Theory (SET) analysis on YDSFs accountability has an understanding of the aspects of hablumminaAllah or vertical accountability that can be seen from a spiritual dimension. In the aspect of hablumminannas or horizontal accountability can be seen from two dimensions namely, program accountability, and finance. This study also illustrates the practices and forms of accountability in accordance with applicable regulatory standards in accordance with Maqashid Syariah as seen from sharia regulations and positive law namely Al-quran, As-sunnah, PSAK 109 and government regulations.Keywords: Accountability Dimension; LAZ, Maqashid Syariah; shariah enterprise theory